DAMPAK KINERJA GABUNGAN KELOMPOK TANI TERHADAP TREND HASIL PRODUKSI KOMODITAS PERKEBUNAN DAN TINGKAT KESEJAHTERAAN PEKEBUN DI KECAMATAN SALAMAN KABUPATEN MAGELANG TAHUN 2014 - Afiat, Abu Rizal (Pendidikan Geografi, 2014)
The purpose of this study was to: 1) determine the performance of the farmer combined group in District Salaman, 2) determine the production trend of plantation commodities in District Salaman, and 3) determine the planters welfare level in District Salaman. This study used a qualitative descriptive method with spatial approach. Constancy of data in this study was maintained using a scoring system. The population in this study were all farmer combined group in District Salaman. Farmer combined group?s sample is 6 sample and as many as 60 planter. Sampling technique using purposive sampling. Techniques of data collection using questionnaires, interviews, and observations. Data analysis techniques to determine the performance and welfare level is a scoring technique. Comparative analysis technique used to determine the production trend of plantation commodities. Results of the study are: 1) There are 3 classes of farmer combined group?s performance in District Salaman, namely intermediate performance as much as 4 farmer combined group, 1 farmer combined group is a beginner, and prime performance as much as 1 farmer combined group. 2) Production trend of plantation commodities increases in 5 villages and decreases in one village. 3) Planters welfare level are divided into 3 categories, namely moderate welfare was as much as 33 planters, 16 planters are lower welfare and high welfare as much as 11 planters.  Keywords: farmer combined group, performance, trend of production, welfare,                    planters